2017
DOI: 10.1016/j.nbd.2017.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory synapse deficits caused by familial α1 GABAA receptor mutations in epilepsy

Abstract: Epilepsy is a spectrum of neurological disorders with many causal factors. The GABA type-A receptor (GABA A R) is a major genetic target for heritable human epilepsies. Here we examine the functional effects of three epilepsy-causing mutations to the 1 subunit (1 A295D22L receptors also exhibited a heightened temperature sensitivity. In addition, the 1 T10'I22L GABA A Rs were refractory to modulation by carbamazepine or midazolam. In agreement with previous studies, we found that22L GABA A Rs were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
(58 reference statements)
1
16
0
Order By: Relevance
“…Given that SAHA readily crosses the blood-brain barrier and is approved by therapeutic regulatory agencies worldwide for human internal use, it seems reasonable to propose that it may be worth investigating as a treatment for epilepsies caused by these mutations. Although SAHA has already been proposed as a candidate therapeutic for the α1 A295D subunit epilepsy mutation (Di et al, 2013 ; Chen et al, 2017a ), the present study extends its potential utility to a new subunit and four new mutations. This prompts us to speculate that proteostasis-enhancing drugs may be worth considering for any GABA A R epilepsy mutation associated with protein misfolding and ER retention.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Given that SAHA readily crosses the blood-brain barrier and is approved by therapeutic regulatory agencies worldwide for human internal use, it seems reasonable to propose that it may be worth investigating as a treatment for epilepsies caused by these mutations. Although SAHA has already been proposed as a candidate therapeutic for the α1 A295D subunit epilepsy mutation (Di et al, 2013 ; Chen et al, 2017a ), the present study extends its potential utility to a new subunit and four new mutations. This prompts us to speculate that proteostasis-enhancing drugs may be worth considering for any GABA A R epilepsy mutation associated with protein misfolding and ER retention.…”
Section: Discussionmentioning
confidence: 75%
“…However, the surface expression of functional α1 A295D β2γ2 GABA A Rs was partially restored by exposure to a 2.5 μM concentration of the proteostatic enhancer, suberanilohydroxamic acid (SAHA, also known as Vorinostat; Di et al, 2013 ). We recently confirmed this by demonstrating in an artificial GABAergic synapse preparation that although α1 A295D β2γ2 GABA A Rs were normally unable to mediate IPSCs, pre-exposure to 0.1 μM SAHA induced α1 A295D β2γ2 GABA A Rs to mediate robust IPSCs that were indistinguishable in magnitude and waveform to those mediated by unmutated α1β2γ2 receptors (Chen et al, 2017a ).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, the peak current for BIX-rescued α1(A322D)β2γ2 receptors amounted to 22% of that for WT receptors, greater than that for SAHA-rescued mutant receptors [ 37 ]. A recent report revealed that despite the relatively modest peak current increase, SAHA treatment restored the receptor kinetics in heterosynaptic cultures harboring the α1(A322D) mutation that were indistinguishable from those harboring the WT receptors [ 38 ]. Therefore, although the physiological relevance of the BIX treatment remains to be established, since previous studies showed that BIX protects neurons from stress-induced cell death [ 51 ], BIX is promising to be further developed to correct GABA A receptor misfolding diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed that application of suberoylanilide hydroxamic acid (SAHA), a FDA-approved drug that crosses the blood-brain barrier, partially restores the function of α1(A322D)β2γ2 GABA A receptors [ 37 ]. Furthermore, the Keramidas group demonstrated that SAHA treatment restored the mutant receptor kinetics similar to wild type (WT) [ 38 ]. SAHA treatment enhanced the folding and trafficking of the α(A322D) subunit post-translationally by promoting BiP and calnexin-assisted folding in the ER in addition to its role in increasing the transcription of the α1(A322D) subunit [ 37 ].…”
Section: Introductionmentioning
confidence: 99%